Biodegradable magnesium Herbert screw – image quality and artifacts with radiography, CT and MRI. Issue 1 (December 2017) - Sonnow, Lena; Könneker, Sören; Vogt, Peter; Wacker, Frank; Falck, Christian
Abstract Background Magnesium alloys have recently been rediscovered as biodegradable implants in musculoskeletal surgery. This study is an ex-vivo trial to evaluate the imaging characteristics of magnesium implants in different imaging modalities as compared to conventional metallic implants. Methods A CE-approved magnesium Herbert screw (MAGNEZIX®) and a titanium screw of the same dimensions (3.2x20 mm) were imaged using different modalities: digital radiography (DX), multidetector computed tomography (MDCT), high resolution flat panel CT (FPCT) and magnetic resonance imaging (MRI). The screws were scanned in vitro and after implantation in a fresh chicken tibia in order to simulate surrounding bone and soft tissue. The images were quantitatively evaluated with respect to the overall image quality and the extent and intensity of artifacts. Results In all modalities, the artifacts generated by the magnesium screw had a lesser extent and were less severe as compared to the titanium screw (mean difference of artifact size of solo scanned screws in DX: 0.7 mm, MDCT: 6.2 mm, FPCT: 5.9 mm and MRI: 4.73 mm; p < 0.05). In MDCT and FPCT multiplanar reformations and 3D reconstructions were superior as compared with the titanium screw and the metal-bone interface after implanting the screws in chicken cadavers was more clearly depicted. While the artifacts of the titanium screw could be effectively reduced using metal-artifact reduction sequences in MRI (WARP, mean reduction of 2.5 mm, p < 0.05), there was no significant difference for the magnesium screw. Conclusions Magnesium implants generate significantly less artifacts in common imaging modalities (DX, MDCT, FPCT and MRI) as compared with conventional titanium implants and therefore may facilitate post-operative follow-up.